Bibliometric analysis of key variables in tourism: Destination, competitiveness, image, quality, and tourist satisfaction (2000-2023) - José Marques Pereira; Paulo Almeida; Giovana Goretti Feijó de Almeida (Administrative Sciences, 2025)
In the scientific literature on tourism, a set of variables is frequently utilized. The objective of this study is to analyze the scenario of scientific publications on these variables between 2000 and 2023. This analysis employs a bibliometric approach, utilizing data collected from the Scopus database. The bibliometric method was employed, with a focus on five variables (tourism destination, competitiveness, image, quality, and satisfaction) and five indicators (author, year, country, journal, and affiliation) essential for mapping research patterns and identifying key trends in the field of tourism. The findings demonstrate that the five variables under examination are inherently interrelated. The image of the destination is of particular importance, as it influences the quality of life of residents and the experiences of tourists, which in turn affects the competitiveness of the destination. The results also demonstrate the multidimensional nature of these variables in shaping tourism destination dynamics. This study underscores the value of bibliometric analysis as a strategic tool for synthesizing and deepening tourism literature. The findings not only highlight the primary research contributions and trends but also identify gaps and opportunities for future research, thereby promoting continuous advancement in tourism knowledge and best practices.
Keywords: 350; competitiveness tourism; destination image; destination quality; tourism destination; tourism satisfaction